Overcoming Divergence in English and French Contract Law: A Common Taxonomy of Commercial Contracts - Pedamon, Catherine (University of Westminster, 2022)
The works presented for the PhD by publication are all connected in the way they engage in a functionally comparative study of the English and French law responses to common problems pertaining to contractual performance and contractual interpretation. My comparative inquiry demonstrates that both France and England have stayed true to their historic responses in times of peace and crisis confirming different mentalités juridiques. As neither England nor France offers ideal solution, parties may be better off finding a resolution to their disputes beyond the legal realm and respond to calls for collaboration. This nevertheless shows persisting differences in Anglo-French approaches. This thesis however argues that these divergences may nevertheless lead to common results through the lens of a taxonomy of commercial contracts – professionally drafted contracts may lead to converging results given the common application and interpretation of frequently used clauses beyond a domestic legal culture; by contrast, rudimentary contracts produce diverging results as the interpretation of these agreements is marked by a distinctive domestic socio-legal culture. This taxonomy has the potential to improve the predictability of outcomes in commercial disputes in England and France.
Keywords: Commercial contracts; Contract law; England; France

International Commercial Law Emerging in Africa - Neels, Jan L. (Potchefstroom Electronic Law Journal, 2022)
This article provides an overview of the history of international commercial law in Africa with reference to instruments of the three sister organisations of private international law (in a wide sense): UNCITRAL (the United Nations Commission on International Trade Law), UNIDROIT (the International Institute for the Unification of Private Law) and the HCCH (the Hague Conference on Private International Law). The adoption of UNIDROIT's Cape Town Convention on International Interests in Mobile Equipment of 2001 is identified as a possible watershed moment in respect of the future development of international commercial law in Africa. Following the creation of an African Continental Free Trade Area by member countries of the African Union, it is suggested that participating states reconsider joining the United Nations Convention on the International Sale of Goods (1980) (CISG) and incorporating the UNCITRAL Model Law on International Commercial Arbitration (1985/2006), which are in a certain sense the two founding documents of the modern lex mercatoria. Another priority, the author suggests, is that Africa needs a supporting instrument on the private international law of contract. The first draft of the African Principles on the Law Applicable to International Commercial Contracts is then discussed with an emphasis on the role of substantive law instruments, in particular the CISG
Keywords: African Principles of Commercial Private International Law; African Principles on the Law Applicable to International Commercial Contracts; International Commercial Law; International commercial contracts; Private international law

Article 255 of the OHADA Uniform Act on General Commercial Law and Consumer Protection: The Need to Experiment - Djieufack, Roland (International Journal on Consumer Law and Practice, 2022)

Influence of current and capital account liberalization on economic growth: Evidence from heavily indebted SSA economies - Leykun, Fentaw (African Journal of Economic and Business Research, 2022)
Capital and current account restrictions were widely used in the past but were largely released during the liberalization movement of the 1990s, as interventionist policies got widespread support that paves the way to the renewed conception of government as an impartial referee. Such a restriction has come back on the agenda with the surge in public debt in the rouse of the Global Financial Crisis. By distorting market signals and incentives, financial repression persuades losses from inefficiency and rent-seeking that cannot be easily quantified. This paper seeks to investigate the impact of current and capital account liberalization on growth, using recent de jure and de facto measures, covering 26 heavily indebted Sub-Saharan African countries over 2000-2020. The results suggest that capital account liberalization escalates growth, brought distributional efficiency in conformity with the neoclassical growth model.
Keywords: Capital account; Current account; Economic growth; Financial liberalization; Financial repression

Exporting the Luxembourg Rail Protocol to the Convention on International Interests in Mobile Equipment to Africa - Otabor-Olubor, Iyare (Uniform Law Review, 2022)
This article recommends the Cape Town Convention on International Interests in Mobile Equipment and appeals to African countries to accede to the Luxembourg Protocol on Railway Rolling Stock (Rail Protocol). The discussion in this article focuses on the extent to which Article XXII of the Rail Protocol can be applied with respect to Africa. The article critically analyses the competence of the African Economic Community (AEC) and its sub-regional organizations to accede to the Cape Town Convention and Rail Protocol. The author provides a detailed argumentative analysis of the legal mandate of the AEC and the influence of African Union (AU) laws on the competence of the AEC’s sub-regional organizations to make declarations under the Cape Town Convention and Rail Protocol. The analysis confirms that competence to accede to the Convention and Rail Protocol resides with sovereign States in Africa and not with the AU, the AEC, the Organisation pour l’harmonisation en Afrique du Droit des Affaires, or any existing sub-regional organization in Africa.

Factors affecting the probability of formalizing informal sector activities in Sub Saharan Africa: evidence from World Bank enterprise surveys - Moyo, Busani (African Journal of Economic and Management Studies, 2022)
Purpose This study aims to investigate the factors that affect the likelihood of formalizing informal sector activities in 13 Sub-Saharan African countries, using World Bank enterprise survey data collected between the periods 2009 and 2018. Notwithstanding the great contribution of the informal economy in Africa, developing countries may stand to gain more if they make inroads in formalizing the informal sector. Design/methodology/approach Since the dependent variable is binary taking the value of one if the firm is willing to formalize and zero otherwise, the study will employ a discrete choice probit model. Findings Results inter alia show that firms that are more likely to formalize are young, owned by individuals with high levels of education and, have registered before. Governments should therefore target firms that are young and provide them with information about the benefits of registration, and if these firms are owned by experienced and educated individuals, the likelihood for them to register would be high. Research limitations/implications The study uses cross sectional data and therefore cannot capture time variant factors affecting the probability to register and also cannot correct effectively for endogeneity. Practical implications Governments should therefore target firms that are young and provide them with as much information as possible about the benefits of registration, and if these firms are owned by experienced and educated individuals, the likelihood to convince them to register would be high. They should also reduce the cost of registration so as to improve net benefits in line with the rational exit view. Social implications Formalizing informal activities will help improve the performance of these firms, reduce vulnerable employment as well as crime, poverty and inequality. Providing decent operating and working conditions to informal players will reduce social and political unrest. Originality/value The African continent is home to many informal firms accounting for roughly 55% of economic activity with 90% of workers eking out a living in a sector that does not respect worker rights, provide decent working conditions and where changes in growth have done little to reduce its size. Regulatory reforms have also been implemented resulting in the number of start-up registration procedures falling from 11 in 2003 to seven in 2019. The uniqueness of Sub Saharan Africa in terms of entrepreneurial culture, political, institutional and economic conditions as well as lack of consensus in the extant empirical literature make this study pertinent.
Keywords: Formalization; Informal; World Bank and Africa

The Limits of Public Contract Law - Casey, Anthony J.; Niblett, Anthony (Law and Contemporary Problems, 2022)
This work received SSHRC funding
Accepted: 2023-06-19T20:16:27Z

The conclusion of contracts by electronic agents in the age of the Fourth Industrial Revolution : a South African perspective - Doughan, Albert Nana (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Commercial law; Contracts; Electronic data interchange; Industry 4.0

The Processes of Democratization and Economic Development in Africa: A Case Study of the Democratic Republic of Congo (DRC) Since 2006 - Otshudi Talo, Esperance (Near East University, 2022)